Investigating sensory modalities in fatigue driver warning systems - Zuki, F.S.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
Driving while feeling fatigue or drowsy may increase the chance to end up in serious accident, resulting in fatality or serious injuries. Many detection and monitoring systems have been developed for fatigue drivers but not many are focusing on sensory modalities to be used as feedback to alert the drivers. By providing multiple channels for receiving information, such a feedback could shorten the drivers' response time, balance out their mental workload, and decrease the miss of warning. This paper examines reported work on existing warning systems, and the associated sensory modalities feedback involved that alert fatigue drivers. Literature review reveals that most systems exploit visual and auditory feedback to alert the drivers but suggests that tactile sensory modalities being far more effective for in-vehicle warning system. Discussion with reference to the recommended sensory modalities as suggested by previous studies were made to understand more about the basic requirements of designing fatigue driver warning systems. This study helps in determining the direction for future work in designing better combination of multisensory modalities for in-vehicle warning systems, in general, and alerting fatigue drivers, in particular. © 2016 IEEE.